Does Entrepreneurship Education Have Impact on Opening and Maintaining A Garment Business Strategy? - Maula, Farij Ibadil; Wardana, Ludi Wishnu; Wibowo, Agus (Universitas Ciputra Surabaya, 2019)
This article aims to analyse the extent of the role of Business Education in upgrading to improve and enhance clothing convection businesses. This article uses descriptive qualitative methods. There were eight sampling participants in the study, including owners and participants of clothing convection businesses. Data analysis was carried out through observation, documentation, and in-depth interviews with participants. The results showed that Business Education did not significantly affect businessmen to open a garment business. The work environment and experience including the educational background of the owners, which varied from elementary school graduate to undergraduate, influenced them to open a garment business Businessmen open garment business because they follow trends, family offspring, continuing friends’ businesses, and their great passion. In the strategy of maintaining a garment business, businessmen need Business Education. It is proven by the fact that these owners often participate in screen printing and sewing seminar workshops, read business books, and get business education through field discussions.